First Report of Nocardia beijingensis Infection in an Immunocompetent Host in the United States - Crozier, Jennifer A. (American Society for Microbiology, 2014)
Here we describe the first reported case of Nocardia beijingensis infection in the United States, made rarer by its presence in an immunocompetent patient.